Bacteriological investigation of pyometra of Black Bengal goats obtained at slaughter - Uddin, ABMJ; Nooruzzaman, M; Akter, T; Khan, MAHNA; Hossain, MM (Bangladesh Veterinarian, 2019)
Nine uteri of Black Bengal goats (Capra hircus) affected with pyometra were collected from three slaughterhouses at Kishoreganj district of Bangladesh. Both horns of each uterus were washed with phosphate buffered saline for isolation and identification of bacteria and its load. The bacterial loads in the uterus were high, ranging between 1 × 107 and 2.8 × 107. Six different bacterial species were identified and confirmed by Polymerase Chain Reaction (PCR). There were five Escherichia coli, six Streptococcus sp., five Staphylococcus sp, one Salmonella sp., one Pasteurella sp. and one Bacillus sp. All had mixed infections containing two or three types of bacterial pathogens. Further studies are needed for the virulence determination and antibiogram profiles. The Bangladesh Veterinarian (2019) 36(1 - 2): 1-7